2017
DOI: 10.1128/aac.01573-17
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Staphylococcus aureus Response to Antimicrobials by the Candida albicans Quorum Sensing Molecule Farnesol

Abstract: In microbial biofilms, microorganisms utilize secreted signaling chemical molecules to coordinate their collective behavior. Farnesol is a quorum sensing molecule secreted by the fungal species and shown to play a central physiological role during fungal biofilm growth. Our pervious and studies characterized an intricate interaction between and the bacterial pathogen , as these species coexist in biofilm. In this study, we aimed to investigate the impact of farnesol on survival, biofilm formation, and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 67 publications
(80 reference statements)
4
94
0
4
Order By: Relevance
“…Another factor that may have contributed to this higher susceptibility is associated to norA downregulation found for cells exposed to functionalized surfaces (VAN and MIX), which was kept over time. Although the expression of norA has been mainly associated with increased tolerance and efflux of a wide variety of structurally unrelated compounds (hydrophilic fluoroquinolones, benzalkonium, ethidium bromide and rhodamine) that does not include vancomycin, [48] the expression of the Nor-family efflux pumps is not fully understood and is likely influenced by several of host and environmental conditions [56,57]. Indeed, Kong et al have reported that S. aureus tolerance to vancomycin treatment was attributed to upregulation of this drug efflux pump [57].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may have contributed to this higher susceptibility is associated to norA downregulation found for cells exposed to functionalized surfaces (VAN and MIX), which was kept over time. Although the expression of norA has been mainly associated with increased tolerance and efflux of a wide variety of structurally unrelated compounds (hydrophilic fluoroquinolones, benzalkonium, ethidium bromide and rhodamine) that does not include vancomycin, [48] the expression of the Nor-family efflux pumps is not fully understood and is likely influenced by several of host and environmental conditions [56,57]. Indeed, Kong et al have reported that S. aureus tolerance to vancomycin treatment was attributed to upregulation of this drug efflux pump [57].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we demonstrated that in a mixed biofilm, the matrix composed of secreted fungal cell wall polysaccharides, conferred coexisting S. aureus cells with enhanced tolerance to antimicrobials [12]. However, findings also indicated that other C. albicans secreted effectors also play a central role in mediating the process, which we identified to be the secreted quorum-sensing molecule farnesol [11].…”
Section: Introductionmentioning
confidence: 74%
“…The opportunistic fungal and bacterial pathogens Candida albicans and Staphylococcus aureus, respectively, are the most frequent combination of organisms co-isolated from various niches in the human host [1][2][3][4][5][6]. Our previous in vitro and in vivo studies have characterized dynamic and complex interactions between these species with important clinical and therapeutic implications [7][8][9][10][11]. More recently, we demonstrated that in a mixed biofilm, the matrix composed of secreted fungal cell wall polysaccharides, conferred coexisting S. aureus cells with enhanced tolerance to antimicrobials [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations